Influence of Water on the Structure and Dielectric Properties of the Microcrystalline and Nano-Cellulose - Kostiantyn M. Kovalov; Olexander M. Alekseev; Maxim M. Lazarenko; Yu F. Zabashta; Yurii E. Grabovskii; Sergii Yu Tkachov (Nanoscale Research Letters, 2017)
Abstract Influence of water in the different states on a structure and dielectric properties of microcrystalline cellulose were studied by of X-ray, thermogravimetry, and dielectric spectroscopy. At research of microcrystalline cellulose (MCC) with different content of water, it is shown that the molecules of water are located in the macropores of MCC and in multimolecular hydrated layers. It is shown that at the increase of concentration of water in a hydrated shell, the reorganization of molecules of cellulose in the surface of crystallites takes place, and as a result, their transversal size and crystallinity increase. It is shown that during the concentration of water, more than 13% in a continuous hydrated shell of crystallites appears. Temperature dependences of actual and imaginary parts of complex dielectric permittivity were studied in the interval of temperatures [−180 ÷ 120] °C on frequencies of f = 5, 10, 20, and 50 kHz. A low-temperature relaxation process and high-temperature transition were observed. Low-temperature relaxation process which is related to transition of surface methylol groups of molecules of cellulose conformation from tg to tt is shifted toward low temperatures at the increase of concentration of water in microcrystalline cellulose.